Challenging obesity: Patient, provider, and expert perspectives on the roles of available and emerging nonsurgical therapies. (July 2015) - Apovian, Caroline M.; Garvey, W. Timothy; Ryan, Donna H.
Abstract : Objective: Adult obesity is recognized as a chronic disease. According to principles of chronic disease management, healthcare professionals should work collaboratively with patients to determine appropriate therapeutic strategies that address overweight and obesity, specifically considering a patient's disease status in addition to their individual needs, preferences, and attitudes regarding treatment. A central role and responsibility of healthcare professionals in this process is to inform and educate patients about their treatment options. Although current recommendations for the management of adult obesity provide general guidance regarding safe and proper implementation of lifestyle, pharmacological, and surgical interventions, healthcare professionals need awareness of specific evidence‐based information that supports individualized clinical application of these therapies. More specifically, healthcare professionals should be up‐to‐date on approaches that promote successful lifestyle management and be knowledgeable about newer weight loss pharmacotherapies, so they can offer patients with obesity a wide range of options to personalize their treatment. Accordingly, this educational activity has been developed to provide participants with the latest information on treatment recommendations and therapeutic advances in lifestyle intervention and pharmacotherapy for adult obesity management. Design and Methods: This supplement is based on the content presented at a live CME symposium held in conjunction with ObesityWeek 2014. Results: This supplement provides an expert summary of current treatment recommendations and recent advances in nonsurgical therapies for the management of adult obesity. Patient and provider perspectives on obesity management are highlighted in embedded video clips available via QR codes, and new evidence will be applied using clinically relevant case studies. Conclusions: This supplement provides a topical update of obesity management, including clinical practice examples, for healthcare professionals who treat or provide care for adults with obesity.